Enhancing wear resistance of TiN coating by gradient bias voltage and arc-enhanced glow discharge. Issue 6 (15th March 2022) - Wang, Y.H.; Guo, F.; Ren, H.; Hu, S.Y.; Chen, Y.J.; Zhao, Y.H.; Gong, F.; Xie, Z.W.
Abstract: The novel gradient bias voltage (GBV) and arc-enhanced glow discharge (AEGD) techniques were used to refine the growth structure and improve the wear resistance of TiN coatings synthesized by applying arc ion plating (AIP). Results showed that TiN coatings without using the GBV + AEGD technique possessed a coarse surface and loose texture with numerous micro-particles and pinholes, which severely degraded the fracture toughness, leading to poor wear resistance. However, the GBV + AEGD duplex technique significantly refined the structure of the TiN coating, resulting in a smoother surface and denser growth texture. The refined texture showed higher H/E and H 3 /E 2 values, leading to good fracture toughness and outstanding wear resistance. The results of this study clearly show the considerable potential of the GBV + AEGD duplex technique in refining the structure and enhancing the anti-wear properties of AIP coatings.